Vita de Flávio Josefo: uma narrativa de autorrepresentação (94-101 d.c.) - Silva Júnior, Valter Bueno da (2015)
We will discuss about the representations of Flavius Josephus from his autobiographical work Vita, and how it has defined and consolidated the perception of self representation of the author. The historical context in which it belonged should be considered. It is about to observe the Judean environment that preceded the Jewish Revolt marked by social, economic and political conflicts, as these were crucial for that the clash between Romans and Jews occurred. Therefore, we noted the surge of the Jewish Revolt, and also the participation of Josephus at that war. In this sense, Josephus experiences in the Revolt are recurrent due to own unfolding of the conflict as he experienced the different sides of the war and witnessed the Roman victory beside them. This way, we will consider the relevance of Josephus' Vita as it was a work that approached the Revolt in a personal perspective, and from it, his memories were highlighted in a constructive process of narrative argumentations, making them the key elements in the very representation of Josephus' impressions. We understand how Josephus' autobiographical speech expresses his own demands of his contemporary, from the relation between narrative, memory, representation and identity.